PERBANDINGAN KARAKTERISTIK MORFO - FISIOLOGI BUAH DAN DAUN JABON MERAH (Anthocephalus macrophyllus ROXB.) DI DUA LOKASI KEBUN MASYARAKAT DI KECAMATAN GANE BARAT DESA LEMO-LEMO DAN KECAMATAN BACAN TIMUR SELATAN DESA PIGARAJA - Lapanji, Ugiyana; Kurniawan, Andy; Umasugi, Buhari; Soenarsih, Sri; Rahmawaty, Aisjah Radin; Hadun, Ramli (Jurnal Pertanian Khairun, 2024)
Red Jabon is a type of wood producing tree that has fast growth. The physical conditions of different environments have an influence on the morpho-physiological characteristics of a plant. The aim of this research is to determine the morpho-physiological characteristics of red jabon fruit and leaves as well as a comparison of the morpho-physiology of red jabon fruit and leaves in Gane Barat District, Lemo-Lemo Village and Bacan Timur Selatan District, Pigaraja Village. Research procedures include sampling and observing morphological and physiological analysis. Data analysis was carried out randomly by looking for the average value and range of each morphological and physiological variation. The results of the research show that the morpho-physiological characteristics of red jabon fruit and leaves include dark green, green, yellowish green, leaf length 14 - 47 cm and 15 - 46 cm, leaf width 10 - 30.2 and 8 - 47.2 cm, stalk length 3 - 5.5 cm and 1 - 5.3 cm, leaf tips have the same pointed shape, broad leaf bone pattern is pinnate, leaf surface texture is rather smooth and uneven, tree diameter between 19-26 cm, 27-34 cm and 35-42 cm, The leaf shape is ovate with a width of 21 cm, oval and asymmetrical. Comparison of characteristics in Lemo-Lemo Village and Pigaraja Village, namely that there are differences in leaf tips, leaf length, leaf bone patterns, leaf surface texture, leaf width, fruit weight and tree diameter, while there are no differences at the base of the leaves